The Association of the Exposure to Work-Related Traumatic Events and Work Limitations among Firefighters: A Cross-Sectional Study - Mi-Ji Kim (International Journal of Environmental Research and Public Health, 2019)
Many firefighters suffering from traumatic events while on duty participate in the work force. However, the impact of work-related traumatic events on work performance is unclear. To address this issue, we administered a work-related traumatic event experience survey, the health-related work limitations questionnaire, the Korea Depression Scale, and the World Health Organization quality of life assessment to firefighters from four cities in Korea. The health-related work limitations questionnaire measured limitations in their ability to perform three specific work demands—physical, psychosocial, and environmental. Of 685 firefighters enrolled in the study, 618 (90.2%) were included in the final analyses. Their mean age ± standard deviation (SD) was 41.1 ± 8.0 years and mean employment period ± SD was 163.0 ± 101.2 months. A large percentage of participants reported they had experienced work-related traumatic events. Among the firefighters, the total work limitation prevalence was 21.5%, 16.8% of them were limited in their abilities to perform physical work demands, 15.5% were limited in performing psychosocial work demands, and 13.8% were limited in their abilities to function without difficulty within the ambient work environment. Based on multivariable logistic regression, with having work-related traumatic event experience of a threat or injury to self, the odds ratio (OR) of having work limitations in physical (OR = 3.32, 95% CI = 1.17–9.41), psychosocial (OR = 3.05, 95% CI = 1.08–8.61), environmental (OR = 4.89, 95% CI = 1.66–14.40) work demands, and total work limitation (OR = 3.73, 95% CI = 1.44–9.68) increased significantly. With experiences of treating fatalities or injured patients, the OR of total work limitation increased significantly (OR = 2.07, 95% CI = 1.09–3.91). We demonstrated a relationship between the firefighters’ exposure to work-related traumatic events and their work limitations. A professional care management system for firefighters to prevent and manage work-related traumatic events should be developed in order to protect and improve their performance ability.